Analisis Permasalahan Sarana dan Prasarana Musik di Sekolah RA Al Mukhlisin - Anggraini, Elya Siska; Wardani, Dwie Nola; Nisa, Khoirun; Julafni, Mia; Nasution, Nayla Amanda (Madani: Jurnal Ilmiah Multidisiplin, 2024)
The problem of music learning facilities and infrastructure in early school is one of the obstacles in developing children's talents and interests in the field of music. This research aims to analyze the problems faced by the RA Al-Mukhlisin school regarding music facilities and infrastructure and their impact on the learning process. The research method used is a literature study, where data is obtained from various journal sources and scientific articles. The results of the research show that limited musical instruments, inadequate condition of the instruments, and lack of teaching materials are the main factors that hinder music learning at RA Al-Mukhlisin. This research provides recommendations for improving the quality of facilities and infrastructure to support effective music learning.